Morality traits for an ideal nurse manager: A multicentre cross‐sectional study. (18th March 2021) - Comparcini, Dania; Simonetti, Valentina; Tomietto, Marco; Rea, Teresa; Primavera, Matteo; Marcelli, Stefano; Serra, Nicola; Cicolini, Giancarlo
Abstract: Aims: To investigate which morality traits are more important for nurses to determine positive opinions of their nurse manager. Background: People selected morality more often than sociability and competence when forming a positive opinion towards an ideal or a newcomer manager. Methods: A multicentre, cross‐sectional study was carried out by administering two questionnaires to 775 nurses on the influence of morality, sociability and competence traits on their impression formation processes. Results: Regarding nurses' perceptions about the morality, sociability and competence traits of an ideal nurse manager, the total score for morality was 20.0; for sociability, it was 14.2; and for competence, it was 19.6. For nurses' opinions about a new nurse manager, the total score of the morality section was 16.2, which was very similar to the total score of the competence section (mean = 16.1). Conclusion: Morality positively influences nurses' initial impression of an ideal manager, and though it seems to be a necessary condition, it is not sufficient by itself to support the nursing staff's perception towards a new manager. Implications for Nursing Management: Our findings could be useful in better understanding the role of morality in social perceptions and behavioural consequences of staff nurses towards their nurse manager.